SINGLE PORT LAPAROSCOPIC CHOLECYSTECTOMY: TECHNICAL ASPECTS AND RESULTS - FAVARO,Murillo de Lima (2018)
ABSTRACT Background: The search for less traumatic surgical procedures without compromising efficacy and safety, together with the technological advances and greater experience of the teams, led to the development of operative techniques with increasingly smaller incisions, the so-called “minimally invasive surgeries”. Aim: To evaluate the technical aspects and results of single port cholecystectomy. Method: Were analyzed 170 patients between 18-74 years submitted to videolaparoscopic cholecystectomies by single port, regardless of elective or urgent indication, without restriction of patient selection. Results: Among the 170 operations, 158 were exclusively performed by single port, and the conversion rate was 7% (inclusion of other accessory trocars or conversion to multiportal). Conversion to open surgery occurred in three cases (1.76%). The mean surgical time was 67.97 min, showing a marked decrease when was reached close to 50 cases and a stabilization after 100 surgeries. The overall complication rate was 10%, with minor complications such as: incisional pain, hematomas, granulomas, port access hernias (9.41%). Conclusion: Single port cholecystectomy can, after standardization and surgical team training, be a safe surgical procedure associated with a recognized aesthetic advantage.